PERANAN AUDIT INTERNAL DALAM MENINGKATKAN PENERAPAN PRINSIP GOOD GOVERNANCE DI KANTOR DINAS KEHUTANAN PROVINSI SUMATERA UTARA - Nurliana Nababan; Ratna Sari Dewi (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2023)
The research conducted aims to determine the role of internal audit at the North Sumatra Provincial Forestry Office. Aims to find out the role of internal audit in improving the application of the principles of good governance at the Office of the Forestry Service of North Sumatra Province. Type of Qualitative Descriptive Research The research subjects were the North Sumatra Provincial Forestry Office and the object is the head of the substance of the finance section, treasurer and three employees of the finance section. The data collection technique used in this study was by using interviews, observation and library techniques. The analysis technique used is by first collecting data, data reduction, data presentation and drawing conclusions or verification so as to provide a clear picture of the problem under study. The results of the study can be concluded that there is a role for Internal Audit in enhancing the principles of Good Governance at the Provincial Forestry Office of North Sumatra Province. Research results also provide information that the importance of good governance in measuring the success of each employee's performance.